Personality Structure of Arthur Fleck as the Main Character in the Film Joker by Todd Phillips - Malinda, Bianca; Nirwan, Nirwan; Wulan, Nawak (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
This research analyzes the narrative elements contained in the film Joker by Todd Phillips and the personality structure of Arthur Fleck as the main character in the film Joker by Todd Phillips. This research aims to find: 1) Describe the narrative elements contained in the film Joker by Todd Phillips. 2) Describe the personality structure of Arthur Fleck as the main character in the film Joker by Todd Phillips. The researcher applies a narratological approach and is supported by psychological theory in the literary works of Sigmund Freud. The structuralism method is a method used by researchers to find research results. The results of this research show that in the film Joker by Todd Phillips there are six narrative elements. The six narrative elements include time sequence, space elements, plot, characterization, conflict and objective elements. Then the results of this research show that Arthur Fleck as the main character articulates three personality structures, namely the id aspect, ego aspect and superego aspect. First, the id aspect of Arthur Fleck's personality structure is divided into three types, namely desire, instinct and enjoyment. Second, the ego aspect of Arthur Fleck's personality structure is divided into two types, namely action and satisfaction. Finally, the superego aspect of Arthur Fleck's personality structure is divided into two types, namely good morals and bad morals.